PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 178 PEKANBARU - Zulfikar Rahman; Zariul Antosa; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem of this research is teacher learning process have been used conventional method, less in student involving process, the teacher often uses speaking method, learning came from teacher or source only, learning process didn’t focus and relate to student experiences, learning passively therefore no meaningful in learning process, less of student understood then causes low on student learning result. According to the problem above is required to solve the problem with related methods with student experiences in daily activities, in order to make the meaningful learning. Quantum Teaching Model gives the student opportunity to develop their potencies by using TANDUR frame that can increase learning result of fifth grader student SDN 178 Pekanbaru. The subject of this research is fifth graders student of SDN 178 Pekanbaru 2014 / 2015 within amount 42 students. This research had been done in two cycles. First cycle is done in twice meetings with once cycle of post test. Collecting data instrument of this research was student observation sheets, teacher observation sheets, and cycle of final post test. This research is in Class Activities Research. This research is aim to increase mathematic learning result of fifth graders student SDN 178 Pekanbaru. The result of this research show that Quantum Teaching Model can enhance student learning result of mathematic, improving learning result can be seen with initial data of learning result average was 63,90 and first cycle was 66,86 increased with 2,96 (4,63%) margin. Meanwhile, student learning result on cycle II in average 77,05 increased with 10,19 (15,24%) margin. First cycle of post test that achieved KKM increase 28,58 (80,03%) from 35,71% became 64,29%. On second cycle of KKM achieved student was 85,71% increase 24,42 (33,32%). It means that Quantum Teaching Model can increases learning result of mathematic of fifth graders SDN 178 Pekanbaru.Keywords: Quantum Teaching,Learning Achievement Of Mathematic.